PENGARUH METODE PEMBELAJARAN WHOLE PRACTICE DENGAN MENGGUNAKAN MODIFIKASI PERMAINAN TERHADAP HASIL BELAJAR DRIBBLING SEPAKBOLA (STUDI PADA SISWA KELAS XI SMA NEGERI 1 MENGANTI GRESIK) - ADITA PRASTIYAWAN, EKO (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Basically teaching physical education in the schools conveyed by sports games. Learning materials delivered every step, so the essentials of learning can be achieved by students. When a physical education teacher have some problems because availability of means to supporting learning. A teacher should have the knowledge and skills strategy and structure of the game that could be modified because it is very useful to improve the optimization of student learning. Many learning methods are used in order to improve students' ability to basic motion dribbling. But in reality and in a fact there are many students who still do not understand the learning material.So it needed a learning method in another designed using the game in class XI student who was once the class X State Senior High School 1 Menganti Gresik. The purpose of this study is: 1.) To determine the effect of whole-practice Learning Method Using Modified Games can improve student learning outcomes. 2.) To determine the influence of whole practice learning methods. By Using the game modified the learning outcomes food ball dribbling of class XI State Senior High School 1 Menganti. The subjects in this research were students of class XI State Senior High School 1 Menganti-Gresik  and the samples are 30 students. Judging from statistical calculations conclude that there is a significant effect of whole practice method using a modified game of foodball dribbling towards learning outcomes as  evidenced  from the  values  ??thitung  7,6044  >  ttabel 2, 1444 with a significance level of 0,05. While the greatest effect is found to be 24.14%. Keywords: Method of whole practice with modifications game, learning outcomes, foodball dribbling